EFEKTIFITAS MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA PENYEMBUHAN LUKA PASCA OPERASI SECTIO CESAREA - Citra Adityarini Safitri; Sulis Diana; Faradina; Widya Puspitasari (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Early mobilization is important for postpartum mothers after normal delivery or Sectio Cesarea. That is two hours after giving birth, at that time a mother must sleep on her back then tilt to the left or right then sit and stand. This study aims to determine the relationship between early mobilization and wound healing after cesarean section surgery at RSU Al Islam H.M Mawardi Krian. This research used a cross-sectional method, with a Systematic Random Sampling technique with a sample size of 70 respondents. Data collection was carried out by filling out a questionnaire created by the researcher and filled in by the respondent. The collected data was processed using statistical tests to be analyzed using the chi square test with (α) 0.05. The results of the study showed that almost all respondents carried out early mobilization which was carried out less than 6 hours after cesarean section surgery as many as 69 people (97.2%) and almost all respondents healed wounds after cesarean section surgery in good criteria as many as 68 people (95.8%). %). The results of the rho rank spearmen correlation analysis test show that the p value is 0.000, meaning there is a relationship between early mobilization and healing of SC Eracs surgical wounds at RSU Al Islam H.M Mawardi Krian. The correlation coefficient value obtained was 0.811, meaning that early mobilization and wound healing after SC surgery were very strong. Early mobilization is related to the healing of surgical wounds so it is hoped that health workers will always provide education and provide care to postpartum mothers after SC surgery to increase motivation in mobilizing after SC surgery.